Evaluation of Effectiveness of Leflunomide in the Treatment of Rheumatoid Arthritis - Filiz Eser; Hatice Bodur; Lale Akbulut Aktekin; Ümit Seçkin (Archives of Rheumatology, 2008)
Objective: The aim of this study was to evaluate effects and side effects of LEF in Rheumatoid Arthritis (RA) patients. Patient and Methods: 51 RA patients taking LEF for mono-or combination therapy were investigated retrospectively. Dosage, period of use and other medical therapies were recorded. Erythrocyte sedimentation rates (ESR), C-reactive protein (CRP) levels, number of tender joints and swollen joints were recorded at the beginning, at 6th and 12th months. If LEF stopped, the reasons were investigated. Disease activity scores were calculated with DAS 28 having 3 variables for patients. Results: Thirty one (61%) of RA patients were given monotherapy and 20 (39%) combination therapy. The median DAS 28 values were 4,41±1,3 for the beginning, 3,35±1,1 for 6th month and 3,47±0,9 for 12th month. The improvement of DAS 28 values between the start the 6th and 12th months was statisticaly significant (p= 0,001, p=0,001, respectively). Side effects tcausing medication to be stopped, was seen in 6 patients (11,7%). Elevation of transaminases was seen in 5 patients. These 5 patients were taking combination therapy. Conclusion: These results suggest that LEF is an effective and reliable DMARD for the treatment of RA patients. (Rheumatism 2008; 23: 52-5)